Analisis Kesesuaian Karakter Pada Silabus Dan Buku Teks IPS Kelas V Terbitan Tiga Serangkai Dengan Nilai Karakter Bangsa Di SD Muhammadiyah 23 Semanggi Surakarta - Wahyuningsih, Arfianny, Dra. Ratnasari Diah Utami, M.Si., M.Pd (2017)
The objectives of this study case: (1) to know the suitability of the characters in the syllabus and IPS text book class V published by Tiga Serangkai with the nation's character values in Elementary School Muhammadiyah 23 Semanggi Surakarta, (2) to know the applicability in the syllabus and IPS text book class V published by Tiga Serangkai to strengthening the character of students in Elementary School Muhammadiyah 23 Semanggi Surakarta, (3) to know the constraints and solutions do teachers in the application of characters in the syllabus and IPS text book class V published Tiga Serangkai with the nation's character values at Elementary School Muhammadiyah 23 Semanggi Surakarta. This type of research is a qualitative descriptive study. The design of this research is the study of documents and case studies, usingsyllabus and IPS text book of class V published Tiga Serangkai. Data analysis techniques using models, Miles and Huberman. The results of this study are: (1) characters in the syllabus and IPS text book class V published Tiga Serangkai has a conformity with the nation's character values, (2) application of syllabus and IPS text book class V published Tiga Serangkai related to the strengthening of character students have applied to teachers with good and there have been planting the national character, (3) constraints in the implementation of the characters on the subjects of IPS in class V is the influence of the environmental of the community lack of supervision, parents at home, and the atmosphere of the class, whereas the solution to overcoming constraints on the application of the character in the class V is the embed example peilaku both from teachers, families, and the environment, in cooperation with parents, teachers familiarise students read a Juz 'Amma, praying Duha, and prayed before the study began.